Membaca Peran Teori Ekologi Bronfenbrenner dalam Menciptakan Lingkungan Inklusif di Sekolah - Dwitya Sobat Ady Dharma (SPECIAL: Special and Inclusive Education Journal, 2022)
An influential figure in the field of education in understanding the diversity of children is Bronfenbrenner who suggested ecological theory. This theory offers a multidimensional model to understand the influence of the family, the environment to a larger circle, for example the state economy and politics, as well as a way of understanding the journey of human life from childhood to adulthood. In this theory, the ecological framework allows us to analyze information about individuals and understand systemic relationships over time. In the dynamics of inclusive schools, this theory can provide a basic understanding of student diversity which is increasing day by day in inclusive schools. If we understand this theory, we can find out the various factors that influence the success of inclusive education. In addition, this theory can also be a reference in setting up an environment that is open to differences, considers diversity as something natural, and supports each other on the uniqueness of each individual in the school context.